Appraisal of Coronavirus on Global Economy - Abdullahi Akanmu (AlQalam Journal of Medical and Applied Sciences, 2020)
Background and objective: This study examines the major challenges of Global economic growth and economic development in all across the globe before coronal virus and how the global actors affect some part of third world countries since feudalism jettisoned as mode of production to the adoption of capitalism that stands as historical background of global economy. It also looks how capitalism was later pioneered to imperialism, slave-trade, colonialism, and neo-colonialism in the global south and some part of global north. Methods: The historical background of corona virus, its negative effects and its way-out to the global economy are also examined in the paper. The secondary source of data adopts as methodology which is qualitative in nature in order to fill knowledge gap in the nature of global economy and impact of corona virus (covid-19) in both Northern and Southern part of the world. Results: This study recommends both Southern and Northern to adjust for one another without imperialism. We also appeal to all global South to adopt solidarity in socio-political economics and military coalition/alliance. Conclusion: The study concludes to commend Worth Health Organization (WHO), UNICEF, World Bank, UN, EU, AU, IMF, OAU, OPEC, and International trades Organization and all Global Centers for Disease Controls, for their effort on Coronal virus and they should also continue to give assistances across the globe.